Vivência do tempo: ciberespaço e usuários - Baptista, Ana Carolina Haddad (2008)
The users of cyberspace are not few that they testify to experience the time in very special way when they are immersed in the navigation processes. It is known, in fact, that the new languages and the new instantaneous processes of recovery and access to the information, that had emerged with the digital technologies, provide new types of experience of the time. This project considers to investigate the main changes in the subjective time tried by the users of cyberspace, in its immersive processes. However, if this universe, made of incessant flows of information, propitiates subjective changes in the experience of the time, must exist objective factors in cyberspace, characteristic in the ways as the experiences of the time can be given to the navigation processes consequently and that them are proper. This research search to examine some of these objective factors for, then, taking these factors as parameters, to analyze, from questionnaires and other instruments of gauging near to the users, as such factors are perceived and internalized under the point of view of the time